2022
DOI: 10.3390/cells11040718
|View full text |Cite
|
Sign up to set email alerts
|

miR172 Regulates WUS during Somatic Embryogenesis in Arabidopsis via AP2

Abstract: In plants, the embryogenic transition of somatic cells requires the reprogramming of the cell transcriptome, which is under the control of genetic and epigenetic factors. Correspondingly, the extensive modulation of genes encoding transcription factors and miRNAs has been indicated as controlling the induction of somatic embryogenesis in Arabidopsis and other plants. Among the MIRNAs that have a differential expression during somatic embryogenesis, members of the MIRNA172 gene family have been identified, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 130 publications
(219 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, we observed differentially expressed miRNAs in early and late seed development among miRNA families which are normally involved in plant growth and development (Plotnikova et al 2019 ; Dong et al 2022 ; Verma et al 2022 ); thus, broadening the range and data availability of miRNAs in oilseed rape development, for example, miR172 regulates not only the flowering time pathway, but also embryo development by controlling APETALA 2 ( AP2 ) and AP2-like genes such as TOE2 (Boutilier et al 2002 ; Shivaraj et al 2018 ; Nowak et al 2022 ) was found in our study. miR165/166 families control leaf adaxial/abaxial development and embryogenesis by targeting the class III homeodomain leucine zipper (HD-ZIP III) transcription factor gene family which includes the REV , PHV and PHB (Wang et al 2007 ; Tang et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed differentially expressed miRNAs in early and late seed development among miRNA families which are normally involved in plant growth and development (Plotnikova et al 2019 ; Dong et al 2022 ; Verma et al 2022 ); thus, broadening the range and data availability of miRNAs in oilseed rape development, for example, miR172 regulates not only the flowering time pathway, but also embryo development by controlling APETALA 2 ( AP2 ) and AP2-like genes such as TOE2 (Boutilier et al 2002 ; Shivaraj et al 2018 ; Nowak et al 2022 ) was found in our study. miR165/166 families control leaf adaxial/abaxial development and embryogenesis by targeting the class III homeodomain leucine zipper (HD-ZIP III) transcription factor gene family which includes the REV , PHV and PHB (Wang et al 2007 ; Tang et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, F-box and GCN-4 were shown to be involved in cell cycle regulation and circadian control [67]. Furthermore, interaction analysis of BTB genes with V. vinifera-specific miRNAs revealed that selected BTB genes were targeted by various development-and stress-related miRNA families, such as vvi-miR169, vvi-miR172, vvi-miR399, vvi-miR482, vvi-miR535, vvi-miR390, vvi-miR395 and vvi-miR408 (Figure 7) [68][69][70][71][72][73][74][75][76][77][78][79]. In our study, we performed in silico analysis, which suggested the potential role of BTB genes in the regulation of different developmental stages and biotic and abiotic stresses in V. vinifera.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis , miR156/7 and miR172 play roles in the juvenile and adult stages of vegetative development, with miR172 acting downstream of miR156. Dynamic antagonistic expression of the miR156 and miR172 families controls the transition from the vegetative to reproductive stages [ 21 , 50 ]. Both the [ 44 ] miRNA156/7 and miR172 families are highly conserved across plant species [ 30 ].…”
Section: Discussionmentioning
confidence: 99%